PENGARUH PENDIDIKAN KESEHATAN PERTOLONGAN PERTAMA KERACUNAN PESTISIDA TERHADAP TINGKAT PENGETAHUAN PETANI DI DESA PESAYANGAN KECAMATAN WANAYASA KABUPATEN BANJARNEGARA - Aldi Indra Lukmana; Nurul Fatwati Fitriana (Universitas Pahlawan, 2023)
Pesticide poisoning is an event that must be given first aid measures to prevent the severity of what happened to victims of pesticide poisoning.To determine the effect of first aid health education on pesticide poisoning on the level of knowledge of farmers in Pesayangan Village, Wanayasa District, Banjarnegara Regency. This research is a quantitative study using a pre-experimental design through one group pre-test post-test. Respondents in the study were 48 farmers and the instrument used in this study was a questionnaire sheet. the respondents in this study were all men with the majority aged 31-40 years as many as 27 respondents (56.3%), the gender of the most respondents was male, amounting to 48 respondents (100%), and the characteristics based on the last education level at most SD as many as 30 respondents (62.5%). Before being given health education about first aid for pesticide poisoning, 12 respondents (25%) were in the sufficient category and 36 respondents (75%) were in the less category, after being given health education about first aid for pesticide poisoning, 30 respondents (62.5%) were given the results. ) is in the good category, 15 respondents are in the sufficient category (31.3%) and 3 respondents (6.3%) are in the less category. There is an effect of first aid health education on pesticide poisoning on the level of knowledge of farmers in Pesayangan Village, Wanayasa District, Banjarnegara Regency, indicated by the p-value = 0.001.